MANIPUEIRA E TERMOTERAPIA NO TRATAMENTO DE ESTACAS DE MANDIOCA ATACADAS POR COCHONILHAS - Razafindrakoto, Charlotte; Ponte, José Júlio da; Andrade, Neilza Campos de; Silveira Filho, José; Gomes, F. Pimentel (REVISTA DE AGRICULTURA, 2015)
MANIPUEIRA E TERMOTERAPIA NO TRATAMENTO DE ESTACAS DE MANDIOCA ATACADAS POR COCHONILHAS